2016
DOI: 10.2527/jas.2016-0487
|View full text |Cite
|
Sign up to set email alerts
|

Feeding microalgae meal (All-G Rich™; Schizochytrium limacinum CCAP 4087/2) to beef heifers. I: Effects on longissimus lumborum steak color and palatibility12

Abstract: The objective of this study was to examine effects of 4 levels of microalgae meal (All-G Rich, CCAP 4087/2; Alltech Inc., Nicholasville, KY) supplementation to the diet of finishing heifers on longissimus lumborum (LL) steak PUFA content, beef palatability, and color stability. Crossbred heifers ( = 288; 452 ± 23 kg initial BW) were allocated to pens (36 pens and 8 heifers/pen), stratified by initial pen BW (3,612 ± 177 kg), and randomly assigned within strata to 1 of 4 treatments: 0, 50, 100, and 150 g·heifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 35 publications
4
34
2
Order By: Relevance
“…Blackmon et al (2015) and Kerth et al (2015) both reported differences in the fatty acid profile of beef subprimals; however, these differences were not maintained after ground beef manufacturing. Although the magnitude of DHA increase is not similar to the LL value (Phelps et al, 2016), the increase in the ground beef product would provide more of that fatty acid when compared with a product from a nonsupplemented animal.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Blackmon et al (2015) and Kerth et al (2015) both reported differences in the fatty acid profile of beef subprimals; however, these differences were not maintained after ground beef manufacturing. Although the magnitude of DHA increase is not similar to the LL value (Phelps et al, 2016), the increase in the ground beef product would provide more of that fatty acid when compared with a product from a nonsupplemented animal.…”
Section: Discussionmentioning
confidence: 93%
“…The authors identified microalgae as an alternative to fish oil/ meal. In the first portion of this study, feeding microalgae meal increased DHA and EPA content by a maximum of 850 and 340% in LL steaks, respectively (Phelps et al, 2016). In the current portion of the study, including microalgae at 150 g/d produced a similar maximum EPA content elevation (300%) but did not produce the same increase in DHA (416%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations